2018
DOI: 10.1093/biolre/ioy199
|View full text |Cite
|
Sign up to set email alerts
|

Interferon tau-dependent and independent effects of the bovine conceptus on the endometrial transcriptome†

Abstract: This study investigated bovine conceptus-induced modifications to the endometrial transcriptome related to effects of interferon tau (IFNT), conceptus origin (in vivo vs. in vitro) and conceptus sex. In vitro (IVF) or in vivo (superovulation and artificial insemination, AI) produced blastocysts were transferred into recipient heifers on Day 7 of the estrous cycle. On Day 15, IVF- or AI-derived conceptuses were obtained by uterine flushing and individually placed on endometrial explants in media for 6 h. Explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 102 publications
(157 reference statements)
7
96
0
Order By: Relevance
“…Comparison of this list of differentially expressed genes (DEG) with the common list of genes altered in endometrial explants following culture with 100 ng/ml IFNT or a Day 15 conceptus (from Sánchez et al, 2019b; Fig. 1) indicated that all of the DEG induced in the endometrium by blastocyst-stage embryos are IFNT-stimulated, in contrast to Day 15 when a significant number of IFNT-independent genes are induced (Mathew et al, 2019;Sánchez et al, 2019bsee below).…”
Section: Blastocyst-induced Changes In the Endometriummentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of this list of differentially expressed genes (DEG) with the common list of genes altered in endometrial explants following culture with 100 ng/ml IFNT or a Day 15 conceptus (from Sánchez et al, 2019b; Fig. 1) indicated that all of the DEG induced in the endometrium by blastocyst-stage embryos are IFNT-stimulated, in contrast to Day 15 when a significant number of IFNT-independent genes are induced (Mathew et al, 2019;Sánchez et al, 2019bsee below).…”
Section: Blastocyst-induced Changes In the Endometriummentioning
confidence: 99%
“…This difference is reflected in the fact that in commercial embryo transfer, the majority of in vitro-produced blastocysts are transferred fresh while the majority of in vivo-derived blastocysts are transferred frozen (Viana, 2018). Mathew et al (2019) compared the transcriptomic response of the endometrium following exposure to IFNT or a conceptus derived from the transfer of an in vivo-derived (superovulation and AI) or in vitro-produced (IVF) blastocyst in order to identify novel transcripts dependent and independent on IFNT, conceptus origin and conceptus sex. IVF-or AIproduced blastocysts were transferred into recipient heifers on Day 7 of the estrous cycle.…”
Section: Response Of the Endometrium To In Vivo Or In Vitro Derived Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that there are early IFNT-independent changes to the endometrium (Forde, Carter, et al, 2011;Mathew et al, 2019), as well as during the pregnancy recognition period (Bauersachs et al, 2012). Of these transcripts that were identified as conceptus-specific but independent of IFN exposure, we have identified that CAPG modifies 5 of these.…”
Section: Capg Induces a Transcriptional Response In Bovine Endometriamentioning
confidence: 58%
“…These interactions are predominantly mediated by the pregnancy recognition signal Interferon Tau (IFNT), a type-I interferon produced by the trophectoderm cells which is required to inhibit luteolysis and maintain the CL. In addition to IFNT, which significantly modifies the transcriptome of the endometrium [17,18], other proteins are produced by the conceptus [19,20] coordinated with increased production of IFNT. Moreover, the response of the endometrium to the conceptus as a whole is greater than its response to prolonged exposure to a type I interferon for 3 days in vivo [12,18].…”
Section: Introductionmentioning
confidence: 99%